ANTIBROWNING EFFECT OF THE COMBINATION OF ASCORBIC, CITRIC AND TARTARIC ACIDS ON QUALITY OF MINIMALLY PROCESSED YACON (Smallanthus sonchifolius) - Vasconcelos, Christiane Mileib; Oliveira, Eduardo Basílio; Arantes, Luma Furtado; Rossi, Stephania Nunes; Rocha, Rovena Lebarch; Puschmann, Rolf; Chaves, José Benício Paes (Boletim do Centro de Pesquisa de Processamento de Alimentos, 2020)
Yacon (Smallanthus sonchifolius) presents significant amounts of phenolics and peroxidases, turning the roots very susceptible to enzymatic browning reaction and related losses. In order to limit it, this study evaluated the efficiency of the antibrowning agents ascorbic, citric and tartaric acids in combination, on controlling these reactions, preservation of phenolics and peculiar sensory characteristics. Experimental mixture design was used, with 13 assays and 5 replicates of the center point; the final concentration of each mixture was 0.2 mol.L-1. Sensory (descriptive) and physicochemical (total phenolic, peroxidase activity, color and texture profile) analysis were performed periodically. Sensory analysis indicated that minimally processed yacon treated with antibrowning agents, did not presented variation (p>0.05) on color, yacon flavor, sweet taste, sweet aroma and moisture appearance. For acid taste, acid aroma and astringency, the greater the presence of citric acid, the greater the perception. Brightness and yacon aroma had higher scores in the presence of tartaric acid. For physicochemical analysis, the presence of the agents, independent of concentration allowed to preserve the phenolic compounds, control peroxidase activity and therefore to maintain the light color of the root for 17 days. Regarding instrumental texture, there was no alteration (p>0.05) during the 17 days of storage. Thus, it is concluded that the use of acids isolated or in mixture presented the same efficiency on controlling enzymatic browning; however, to obtain minimally processed yacon with more attributes similar to fresh yacon, a lower concentration of citric acid can be used.